The Mechanism of Downregulation of Twist1 Inhibiting Trophoblast Invasion and Aggravating the Development of Preeclampsia - Yang, Shuangjian; Tong, Wenjuan; Li, Yi (Frontiers in Surgery, 2022)
To study the expression of underexpression of transcription factor Twist1 in preeclampsia (PE) and its effect on the invasion of placental trophoblast cells, and to explore its related mechanism on the development of PE by establishing a pregnant rat model. Collect the villi from the induced abortion in the first trimester (6-8 weeks), the normal placenta (18-20 weeks) induced by the second trimester, the term placenta tissue of normal pregnancy (37-40 weeks), and the placental tissue of patients with preeclampsia (34- 37 weeks), to detect the expression of Twist1. Primary culture of trophoblast cells in placental tissues of normal pregnant women and placental tissues of PE patients. Detect the invasion ability of the two groups of trophoblasts; divide the primary cultured trophoblasts into two groups: an experimental group and a control group. Specific Twist1 siRNA is added to the experimental group, and no reagents are added to the control group. The above-mentioned cells are given different interventions. Cultivate for 72 hours to explore the effect of Twist1 on trophoblast cell invasion. The SD rats were conceived. After the pregnancy was stable, the SD rats in different groups were treated with different treatments (interference with Twist1), and the average systolic blood pressure and urine protein of the gestational mothers in the different treatment groups were measured at one week, two weeks, and full-term pregnancy. To detect the expression of Twist1 in the placenta tissue of SD rats with different interventions at full-term pregnancy. The results showed that Twist1 expression is down-regulated in PE, and the invasion ability of placental trophoblast cells in PE patients is weak. After inhibiting Twist1, the mean tail artery pressure and urine protein level of SD pregnant rats increase, showing a trend of PE. The mechanism may be related to the inhibition of placenta by Twist1 Trophoblast cell invasion ability is related.